Students Under Stress (Why Are Cultural Differences Stressful?) - Amir M. Maleki; Fariborz Rahimnia (Studia i Materiały)
Although acculturative stress (AS) studies have been conducted for five decades, we still know little about it. Moreover, we do not have a specific framework for international student population. The purpose of this paper is to explore how to use theories and research methods in different contexts and develop a framework. We systematically review articles related to this field, particularly 92 studies published until 2020. There are common variables in AS, comprising social, cultural, psychological, communicative, and demographic factors which managers and decision makers should properly understand and administer in organizations. This article also confirms a link between AS and mental and behavioral outcomes. We have elaborately developed a framework including antecedents and outcomes of AS. Suggestions have also been offered for future research.